THE POLITICIZATION OF THE JUDICIARY DURING ZIA-UL-HAQ’S ERA: A PATH TO LEGITIMACY - Ashraf, Zahida (Academic Journal Research, 2025)
Objective: This study investigates the role of the judiciary during General Muhammad Zia-ul-Haq’s military regime (1977–1988), focusing on how judicial institutions were instrumentalised to legitimise authoritarian rule, suppress political opposition, and implement an Islamisation agenda. Method: Employing a qualitative historical-analytical approach, the research critically analyses primary legal documents, constitutional amendments, and landmark court judgments from the Zia era, complemented by secondary scholarly sources. Results: The findings reveal a strategic transformation of Pakistan's judiciary from an independent body into an apparatus serving executive interests. Courts were co-opted through structural changes and doctrinal shifts, such as the validation of martial law under the doctrine of necessity and the endorsement of Islamisation policies, which aligned judicial functions with the regime’s ideological objectives. Novelty: This study contributes original insight into the systematic erosion of judicial autonomy under military rule in Pakistan, highlighting the judiciary’s complicity in legitimising undemocratic governance. By tracing this transformation, the research offers a foundational context for understanding contemporary challenges to judicial independence and civil-military relations in Pakistan’s constitutional development.